Microstructural study of Portland cement partially replaced with fly ash, ground granulated blast furnace slag and silica fume as determined by pozzolanic activity. (30th March 2020) - Nedunuri, Sai Surya Sree Aparna; Sertse, Seifemichael Getachew; Muhammad, Salman
Highlights: Replacement percentages of SCMs were attained considering their pozzolanic activity. Ca(OH)2 consumed per gram of mineral admixture is of order SF > FA > GGBFS. Reactivity of GGBFS in NaOH environment was higher when compared with CH environment. Microstructure and compressive strength were enhanced with incorporation of SCMs. Abstract: Many industrial by-products are widely used these days as supplementary cementitious materials (SCM) with ordinary Portland cement (OPC). These vary in their cementitious potential and hence affect the development of strength and microstructure of the resulting composite with OPC. The characteristics of mineral admixture such as chemical composition, fineness, the amount and rate of consumption of portlandite and the replacement level play a key role in enhancing several properties of the binder system. In this study, the evolution of pore structure with curing age in mortars of OPC replaced with silica fume, ground granulated blast furnace slag and fly ash was studied comprehensively using three different methods: water saturation test, scanning electron microscopy and mercury intrusion porosimetry. The replacement of OPC with SCMs was done with respect to the pozzolanic activity and was obtained by equating the amount of Ca(OH)2 (CH) consumed per gram of mineral admixture to the amount of CH produced per gram of OPC.